Bifid median nerve in a patient with carpal tunnel syndrome: A case report and literature review. Issue 4 (November 2016) - Narayan, Sharwan
Abstract: A middle‐aged man with Carpal tunnel syndrome without any known predisposing risk factors is presented. Ultrasonography demonstrated two structures within the left carpal tunnel with similar echo pattern as median nerve, thus confirming an anatomical variation in the median nerve, described in the literature as bifid median nerve. The knowledge of the existence of bifid median nerve is an important factor in planning surgical decompression of median nerve to avoid nerve and persistent median artery injuries and/or potential relapse if decompression of both branches is not carried out. In addition, this knowledge is important in deciding whether to inject above the bifurcation or into the epineurial of individual nerve trunks in the setting of planned symptomatic corticosteroid injections. In conclusion, bifid median nerve is an anatomic variant that may contribute to carpal tunnel syndrome and can be demonstrated ultrasonographically. It is important to be aware of this anomaly when planning carpal tunnel release surgery and symptomatic corticosteroid injections.